0.2*(x+2)=(1/3)*(3-x)

Simple and best practice solution for 0.2*(x+2)=(1/3)*(3-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.2*(x+2)=(1/3)*(3-x) equation:



0.2(x+2)=(1/3)(3-x)
We move all terms to the left:
0.2(x+2)-((1/3)(3-x))=0
Domain of the equation: 3)(3-x))!=0
x∈R
We add all the numbers together, and all the variables
0.2(x+2)-((+1/3)(-1x+3))=0
We multiply parentheses
0.2x-((+1/3)(-1x+3))+0.4=0
We multiply parentheses ..
-((-1x^2+1/3*3))+0.2x+0.4=0
We multiply all the terms by the denominator
-((-1x^2+1+(0.2x)*3*3))+(0.4)*3*3))=0
We calculate terms in parentheses: -((-1x^2+1+(0.2x)*3*3)), so:
(-1x^2+1+(0.2x)*3*3)
We add all the numbers together, and all the variables
(-1x^2+1+(+0.2x)*3*3)
We calculate terms in parentheses: +(-1x^2+1+(+0.2x)*3*3), so:
-1x^2+1+(+0.2x)*3*3
determiningTheFunctionDomain -1x^2+(+0.2x)*3*3+1
Back to the equation:
+(-1x^2+(+0.2x)*3*3+1)
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*3+1), so:
-1x^2+(+0.2x)*3*3+1
We calculate terms in parentheses: +(-1x^2+(+0.2x)*3*

See similar equations:

| 2×-y-4=03×+y-9=0 | | 1/(x)=0.01 | | 16x^2-24+8=1 | | 1/(x)=0.001 | | 2y=×+35y=×-7 | | 2n+3=18+1 | | -10y+5=50+5 | | 100-(10+10b)=140 | | 16=v3+ 14 | | 4(n-6)-(2-5)=8n | | 7w+2=-2 | | -62(y-)=y+(-25) | | (x-2)(x-5)=(x-1)(X-4) | | 8^(4y+7)=(1)/(64^(9+2y)) | | 2(x+1)-3=13 | | 4x2-x-0.73=0 | | 2(3x+4)=2x+20 | | 19÷a=11 | | 7r=115 | | |1/3-x/4=7/12| | | y=6.75+25•12 | | 3v=14=25 | | 0.26y=0.676* | | x/−2–15=−35 | | 8=2x+29 | | 12=-6+v | | 4x+4(3-5x)=8(4-2x) | | B(x)=30.00-0.05x | | 4x+4(3-5x)=8(4-2x | | x/4=36/5 | | 11=z4 | | 21/4x+(41/3x-74/5)/23/35=0 |

Equations solver categories